CORRIGENDUM - Ejdus, Filip (Journal of Regional Security, 2018)
CORRIGENDUMLakić, Nikola. 2013. “History Education and the Security Community Building in the Western Balkans: A Critical View”, Journal of Regional Security 8 (2): 115−136. In the above-mentioned article, the following corrections should be made: 1. In the first paragraph on page 128, footnote 84 should be added as a reference to the source at the end of the following sentence: “Such a model of national awareness and historical memory creates a specific type of socialization of young people that in the future can lead more easily to conflicts among the neighboring nations than to peaceful settlement.” Footnote 84 should read as follows: “Stojanovic 2001, 28”. 2. In the second paragraph on page 128, footnote 87 should be added at the end of the following sentence: “New history textbooks need not represent a new construction which would replace national histories, but rather a new interpretation of national pasts based more on common Balkan cultural and institutional heritage and providing more room for narratives of cooperation.” Footnote 84 should read as follows: “See more about changes in methods, in Koulouri, 2009”. 3. Footnote 96 should be added at the end of the first paragraph on page 129. Footnote 96 should read as follows: “http://cdrsee.org/projects/jhp”. • Following those corrections all subsequent footnote numbers should be renumbered. • In the reference list at the end of the text, the following sources should be included: “Stojanović, Dubravka. 2001. “History Textbooks and the Creation of National Identity”. In Teaching the History of Southeastern Europe, edited by Christina Koulouri, 27−32. Thessaloniki: Center for Democracy and Reconciliation in South East Europe.” The author and the Editorial Team regret any inconvenience.